PENGARUH KEBIJAKAN TAX AMNESTY , PERTUMBUHAN PERUSAHAAN, RISIKO PERUSAHAAN DAN UKURAN PERUSAHAAN TERHADAP REAKSI PASAR (Studi Pada Perusahaan LQ45 yang Terdaftar di BEI Tahun 2021) - Anna Sofia Atichasari; Umi Kulsum; Sat Yudha Dhahana; Ahmad Bukhori (Jurnal Manajemen FE-UB, 2023)
The capital market is one of the most sought after activities by the people of Indonesia and even the world.Market reactions that are often observed by investors, by avoiding abnormal returns to investments.This study aims to analyze the market reaction that can be seen with Abnormal Return.By selecting the dividend variable, the market reaction by looking at abnormal returns, and also company growth, company risk, and tax amnesty policy as the dependent variable. The population in this study is the LQ-45 Company in 2021 which is listed on the Indonesia Stock Exchange.The sampling technique is Proposive sampling or random selection using criteria. Data collection techniques with secondary data are viewed on company information on the IDX.com website and then analyzed using descriptive statistical analysis and multiple linear regression analysis with the help of the IBM SPSS Version 25.0 program.The results of the research and discussion are 1) based on a simultaneous test of company growth, company risk, and tax amnesty policies have a positive effect on abnormal returns with a significance value of 0.030 < 0.050. 2) The results of the partial test show that the company's growth has a positive effect on abnormal returns with a significant value, company risk has a negative effect on abnormal returns with a significant value of 0.965> 0.050, and Tax Amnesty Policy has a negative effect on abnormal returns with a significant value of 0.296> 0.050. Keywords : Tax Amnesty, Company Growth, Company Risk, Abnormal Return, Capital Market